Occupational factors and markers of testicular function among men attending a fertility center. Issue 4 (11th February 2023) - Mínguez-Alarcón, Lidia; Williams, Paige L; Souter, Irene; Ford, Jennifer B; Ghayda, Ramy Abou; Hauser, Russ; Chavarro, Jorge E
Abstract: STUDY QUESTION: Are occupational factors associated with markers of testicular function among men attending a fertility center? SUMMARY ANSWER: Men working non-daytime/rotating shifts and those with physically demanding jobs have higher sperm concentration and total sperm count as well as higher estradiol and total testosterone concentrations. WHAT IS KNOWN ALREADY: Semen quality has declined during recent decades and has been negatively correlated with higher risks of common chronic diseases and mortality, highlighting its public health importance beyond fertility and reproduction. While most of the previous epidemiology literature on male fertility has focused on environmental exposures, dietary factors, and other related variables, little attention has been paid to occupational factors. STUDY DESIGN, SIZE, DURATION: This observational study included 377 men who were male partners in couples seeking infertility treatment at a fertility center, who enrolled in the Environment and Reproductive Health (EARTH) study between 2005 and 2019. PARTICIPANTS/MATERIALS, SETTING, METHODS: Self-reported information on lifting/moving heavy objects, typical shift, and physical level of exertion at work was collected from a take-home questionnaire. Semen samples were analyzed following World Health Organization guidelines. Enzyme immunoassays were used to assess reproductive hormone concentrations. Linear regression models were used to evaluate the association between occupational factors and measures of testicular function, while adjusting for covariates such as age, BMI, education, race, smoking, and abstinence time, and accounting for multiple semen samples (mean = 2, min–max = 1–9) in analyses for semen parameters. MAIN RESULTS AND THE ROLE OF CHANCE: Men had a median (interquartile range) age of 36 (33, 39) years and were predominantly Caucasian (87%). Of the men who completed the survey, 12% reported often lifting or moving heavy objects at work, 6% reported heavy physical exertion at work, and 9% reported evening or rotating shifts. Men who reported often lifting or moving heavy objects at work had 46% higher sperm concentrations ( P = 0.01) and 44% higher total counts ( P = 0.01) compared with men who reported never lifting or moving heavy objects at work. Similar results were found for men working in rotating shifts compared to those in day shifts, as well as for men involved in heavy levels of physical exertion compared to those with light levels at work. We also found that men involved in heavy/moderate levels of physical exertion at work had higher circulating testosterone concentrations compared to those with lighter exertion (adjusted means of 515 and 427 ng/dl, respectively, P = 0.08), and men who often moved/lifted heavy objects at work had higher estradiol concentrations, compared to those who never did (adjusted means of 36.8 and 27.1 pg/ml, respectively, P = 0.07). Men working evening/rotating shifts had 24% higher testosterone ( P = 0.04) and 45% higher estradiol concentrations ( P = 0.01), compared to men working day shifts. No associations were observed for ejaculated volume, total motility, morphologically normal sperm, or serum FSH and LH concentrations. LIMITATIONS, REASONS FOR CAUTION: Due to our study design which recruited men from couples seeking fertility treatment, it may not be possible to generalize our findings to men from the general population. Also, as is the case of all studies based on self-reported questionnaires, measurement error and misclassification of the exposure are potential concerns. WIDER IMPLICATIONS OF THE FINDINGS: Physically demanding jobs and rotating or evening shift occupations may be associated with higher testicular function in men measured as higher sperm concentrations and counts as well as higher serum testosterone and estradiol levels. Confirmation of these findings in other non-fertility clinic study populations is warranted. STUDY FUNDING/COMPETING INTEREST(S): NIH grants R01ES022955, R01ES009718, R01ES033651, and R01ES000002 from the National Institute of Environmental Health Sciences (NIEHS) and Legacy, Inc. R.A.G. works part time for Legacy, Inc., which provided funds to perform this analysis. There are no other conflicts of interest. TRIAL REGISTRATION NUMBER: N/A.